A Computationally-Derived Model for the Solvatochromism of: P -Phenolates with High Predictive Power - Mera-Adasme, R; Dominguez-Caru, M (Royal Society of Chemistry, 2018)
We report that the positive, reverse or negative solvatochromism of p-phenolate-based dyes is highly correlated with the multireferential (MR) character of their ground-state wave function, with negative compounds presenting the highest degeneracy. CASSCF/NEVPT2 calculations show that the high MR character of the wave-function in negative dyes allows those systems to increase the dipole moment of the ground state by breaking the degeneracy as a response to the field of a polar solvent. The resulting stabilization of the ground-state with increasing solvent polarity leads to the observed negative solvatochromic behavior. A computational indicator based on our results has been successfully used for determining the direction of the solvatochromic shift of 24 dyes. Thus, our work sheds light on the physical-chemical basis for solvatochromism while providing experimental chemists with a practical tool for the design of novel negative, positive or reverse solvatochromic dyes. © 2018 the Owner Societies.